APPLICATION OF THE FREEDOM OF THE PRESS AND THE JOURNALISTIC CODE OF ETHICS - Suprapti Indah Putri (Jurnal Ilmiah Ilmu Komunikasi Communique, 2021)
Media has always deliver the news to criticize harshly various government policies, thereby, it’s no wonder the reporters are often subjected to the action of a reign of terror from people who felt disadvantaged over the released news. This research aims to examine the application of the freedom of the press and the journalistic code of ethics and to study the attitute of WASPADA Online journalist regarding the applied free press and the journalistic code of ethics. In this study, I used a communication theory S-O-R model; Stimulus-Organism-Response, and also adopted the social responsibility theory and individual differences theory as its supporting theory. The researcher used the descriptive method and use the purposive sampling, whereby the researcher distributes questionnaires to 8 WASPADA Online reporters who have 2 years experiences. Based on the results, the WASPADA Online reporters argued that press freedom is a freedom that ensures journalists to express their opinion, facts, and to ensure the safety of the journalists while performing their coverage. Majority of the journalists agree with the existence of freedom of the press, but they still hold on to the Journalistic Code of Ethics, which will be their guide to be a professional journalist.